In vitro and in vivo evaluation of 99mTc-pyrophosphate capability to bind Staphylococcus aureus - Janković Drina Lj; Vukadinović Aleksandar A.; Nikolić Nadežda S.; Vranješ-Đurić Sanja D.; Marković Srđan Z.; Kastratović Dragana A. (Srpsko lekarsko drustvo, 2015)
Introduction: Scintigrafic imaging of infection and inflammation is of special interest in nuclear medicine diagnostic of infectious or inflammatory diseases. For this purpose various radiolabelled compounds have been explored. The aim: The aim of this study was to find out whether 99mTc-PYP posses capability to bind to Staphylococcus aureus, and possibilities for its use in bacterial infection and inflammation not only in non-specific way. Methodology: 99mTc-PYP has been used for imaging infective and non-infective skeletal diseases. Protein binding, lypophilicity measurements and in vitro binding to viable and dead bacteria of 99mTc-PYP with 3 different concentrations of sodium pyrophosphate decahydrate were studied. Wistar rats were used in all biodistribution evaluations. Results: All 99mTc-PYP samples were on high radiochemical purity, with high protein binding and hydrophilic character. In vitro investigations have shown that the uptake of 99mTc-PYP to Staphylococcus aureus was depended on concentration of pyrophosphate decahydrate in the samples. Thus the highest uptake to viable Staphylococcus aureus (>30 %) was obtained in the sample with 0.10 mg pyrophosphate decahydrate/1 ml. The in vivo investigation results on rats shown increased radioactivity in the infected thigh muscle (T/NT>2.3) and intensify bone uptake (5.4 ÷ 6.9 % ID/g). Conclusion: Considering that the diagnosis of bone or joint infection remains a challenging problem, it is obvious how important is to investigate whether 99mTc-PYP could be used as a specific agent for bacterial infection in the axial skeleton.